Multinational finance : evaluating opportunities, costs, and risks of operations - Butler, Kirt Charles (John Wiley & Sons, 2012)
"Multinational Finance, Fifth Edition assumes the viewpoint of the financial manager of a multinational corporation with investment or financial operations in more than one country. This book provides a framework for evaluating the many opportunities, costs, and risks of multinational operations in a manner that allows readers to see beyond the math and terminology surrounding this field to realize the general principles of multinational financial management. Logically organized and written in a clear, non-technical style, this book includes information on international finance topics such as foreign exchange, currency and derivatives markets, currency risk (transaction, operating, and translation) management, country risk, international taxation, capital structure, cost of capital, and international portfolio diversification. It also offers unique chapters on multinational treasury management, the rationale for hedging currency risks, options on real assets, international corporate governance, asset pricing, and portfolio management"--Provided by publisher